2020
DOI: 10.1111/vsu.13395
|View full text |Cite
|
Sign up to set email alerts
|

Partial cystectomy with a bipolar sealing device in seven dogs with naturally occurring bladder tumors

Abstract: Objective: To describe the use of a bipolar sealing device (BSD) for partial cystectomy in dogs undergoing excision of bladder tumors. Study design: Multicenter, prospective, clinical pilot study.Sample population: Seven client-owned dogs with nontrigonal urinary bladder lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 10 publications
0
20
0
Order By: Relevance
“…Furthermore, during urodynamic testing, plateau of intravesicular pressure was most commonly seen with development of normograde leakage from the clamped vulva (female dogs) or sutured urethra (male dogs), suggesting that the stapled cystectomy site was sufficiently strong to resist large volume leakage at higher pressures. The authors suspect that the small volume of leakage observed at the caudal staple line is clinically similar to small volume urine leakage through the needle holes observed with sutured cystotomies and partial cystectomies 6,7 . No catastrophic failures of the cystectomy site were observed during this study; however, it is important to note that our ability to detect catastrophic failure may have been limited by the use of in situ leak pressure testing rather than explanting the urinary bladder and ligating the urethra and ureters to create maximal intravesical pressure by preventing urine outflow through the urethra.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…Furthermore, during urodynamic testing, plateau of intravesicular pressure was most commonly seen with development of normograde leakage from the clamped vulva (female dogs) or sutured urethra (male dogs), suggesting that the stapled cystectomy site was sufficiently strong to resist large volume leakage at higher pressures. The authors suspect that the small volume of leakage observed at the caudal staple line is clinically similar to small volume urine leakage through the needle holes observed with sutured cystotomies and partial cystectomies 6,7 . No catastrophic failures of the cystectomy site were observed during this study; however, it is important to note that our ability to detect catastrophic failure may have been limited by the use of in situ leak pressure testing rather than explanting the urinary bladder and ligating the urethra and ureters to create maximal intravesical pressure by preventing urine outflow through the urethra.…”
Section: Discussionmentioning
confidence: 61%
“…The authors suspect that the small volume of leakage observed at the caudal staple line is clinically similar to small volume urine leakage through the needle holes observed with sutured cystotomies and partial cystectomies. 6,7 No catastrophic failures of the cystectomy site were observed during this study; however, it is important to note that our ability to detect catastrophic failure may have been limited by the use of in situ leak pressure testing rather than explanting the urinary bladder and ligating the urethra and ureters to create maximal intravesical pressure by preventing urine outflow through the urethra. The decision to use a CMG to evaluate leakage pressures in situ was based on the desire to mimic the setting in clinical patients.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Cystectomy is recommended for a number of urinary bladder (UB) affections, including cystic neoplasia, patent urachus excision, iatrogenic injuries, bladder necrosis, recurrent interstitial cystitis, devitalized tissue following bladder rupture, and neurogenic bladder ( Granger et al., 2020 ; Lipscomb, 2018 ; Milovancev et al., 2020 ; Sivacolundhu & Withrow, 2013 ; Tobias, 2011 ). Furthermore, studies reported that more than 30% of incontinent dogs, particularly those who had undergone ovariohysterectomy, had reduced bladder storage function ( Berent & Mayhew, 2017 ; Burrow et al., 2005 ).…”
Section: Introductionmentioning
confidence: 99%